PENGEMBANGAN BUDAYA LOKAL SEBAGAI POTENSI DAERAH MELALUI PROMOSI PARIWISATA DI BUTON TENGAH (Jurnal Common, 2020)
The purpose of this study was to determine the promotion of tourism in the development of local culture as a potential area in the Central Buton district. by using qualitative descriptive analysis methods. Primary data were collected using interviewing techniques with several informants, namely the Head of the Tourism Office, the Head of Promotion and Marketing, the Head of Tourism Destinations, and several local tourists who visited Central Buton. While secondary data is obtained through literature review, namely books, journals and internet sites that have relevance to the object of research. The results of this study indicate that the Central Buton District Tourism Office applies a promotional mix in increasing the number of tourist visits, namely advertising, sales promotions, public relations, personal sales and direct marketing. The supporting factors of promotional activities are the high tourism potential in Central Buton. While the inhibiting factors are inadequate Human Resources such as employment staff, Central Buton that are not too well known by people outside the Buton area, as well as inadequate facilities and infrastructure.